Near-infrared Ag2Se quantum dots with distinct absorption features and high fluorescence quantum yields. Issue 44 (18th April 2016) - Shi, Li-Juan; Zhu, Chun-Nan; He, He; Zhu, Dong-Liang; Zhang, Zhi-Ling; Pang, Dai-Wen; Tian, Zhi-Quan
Abstract : Near-infrared Ag2 Se QDs with distinct absorption features ranging between 830–954 nm and fluorescence quantum yields up to 23.4% were controllably synthesized, and the molar extinction coefficients of the Ag2 Se QDs were determined. Abstract : Near-infrared Ag2 Se quantum dots (QDs) with distinct absorption features ranging between 830–954 nm and fluorescence quantum yields up to 23.4% were controllably synthesized using a phosphine-free approach. Based on the distinct absorption features, the molar extinction coefficients of the Ag2 Se QDs have been determined.